Overview of Public Sector Performance Assessment Processes in Japan - Matsuura, Miki (World Bank, Washington, DC, 2012)
The Government of Japan began introducing evaluation techniques in 2001 within the context of a Central Government reform program that involved the establishment of new ministries and the integration and abolition of existing ministries. Japans approach emphasizes assessing policies and activities, and then incorporating results into future planning and budgeting, with a focus on making public sector programs and activities more efficient. This is a synopsis of Japans experience with public sector performance assessment processes between 2001 and 2010. This note presents a range of initiatives underway in Japan, including policy and activity evaluation, as well as the spending review exercise designed to make public sector service delivery more efficient. The intention of this note is not to necessarily endorse Japans approach, but rather to document it as a case study.